Electrical conductivity and microstructure of NiO-CGO composites prepared by one-step synthesis - Nascimento, Rubens Maribondo do; Macedo, Daniel Araújo de; Figueiredo, Filipe Miguel Lebre; Patrício, Sónia Gonçalves; Martinelli, Antonio Eduardo; Paskocimas, Carlos Alberto; Marques, Fernando Manuel Bico (IOP Publishing, 2013)
The correlation between the microstructure and electrical properties of NiO-Ce0.9Gd0.1O1.95 (NiO-CGO) composites prepared by a one-step synthesis method is reported in the present work, and compared to conventional samples synthesized by mechanically mixing commercial powders. Samples sintered between 1350 and 1450 °C had their microstructures and electrical properties investigated by scanning electron microscopy (SEM) and impedance spectroscopy. The total electrical conductivity in the range of 100 – 500 °C of one-step composites is more than one order of magnitude higher than for conventional material. This result is associated to the presence of a network of well-connected and homogeneously distributed NiO grains shown by SEM for the one-step composite, which is responsible for its improved percolative behavior and lower activation energy (0.24 eV at 250 – 650 °C).
Keywords: propriedades elétricas; condutividade elétrica; microscopia eletrônica de varredura